Influence of different culture media on embryo development following in vitro fertilization of caprine oocytes - YADAV, PARUL; KHARCHE, S D; GOEL, A K; JINDAL, S K (The Indian Journal of Animal Sciences, 2018)
The present study was designed to compare the developmental competence of in vitro fertilized caprine embryos at different cell stages in three different culture medium(TCM-199, mSOF, KSOM). Oocytes were collected from ovaries and matured in TCM-199 medium containing FSH (5 μg/ml), LH (5 μg/ml) and estradiol-17β (1 μg/ml), supplemented with 20% fetal bovine serum at 38.5 °C and 5% CO2 in an incubator under humidified air for 27 h. After 27 h of in vitro maturation (IVM), oocytes were denuded, washed and co-incubated with 50 μl neat semen diluted in 5 ml of sperm TALP containing 20% EGS and 10μg/ml heparin. Oocytes-sperm after 18h of co-incubation were randomly divided into three groups: Group1(TCM-199 containing 10% NCS and 4mg/ml bovine serum albumin), Group 2(Synthetic oviductal fluid containing 10% NCS and 4mg/ml BSA) and Group 3(Potassium simplex optimization medium (KSOM) containing 10% NCS and 4mg/ml BSA) and found the cleavage rate, morulae and blastocyst percentage for groups 1, 2, and 3 were 13.6, 10.14 and 2.41%, 11.7, 7.6 and 3.84% and 31.4, 12.73 and 6.05%, respectively. Statistical analysis revealed that the cleavage rate and embryo development up to morula and blastocyst stage in group 3(KSOM) was significantly higher (P<0.01%) as compare to group1 and group2.